Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade. Issue 16 (29th July 2022) - Muhammad, Naveed; Ur Rahman, Shafiq; Uddin, Hilal; Shehzad, Omer; Ismail, Muhammad; Ali, Niaz; Khan, Aslam; Shahid, Muhammad; Ullah, Abid; Ahmad, Shujaat; Hussain, Haya; ul Haq, Ikram; et al.
Abstract: The antidiarrheal effect of methanolic extract of Trillium govanianum Wall. ex D. Don (Melanthiaceae alt . Trilliaceae) was studied at doses of 12.5, 25, and 50 mg/kg in different animal models of diarrhea including castor oil (6 mL/kg), magnesium sulfate (2 gm/kg), sodium picosulfate (2 mL/kg) and lactitol (0.25 mL/kg). The antispasmodic effect of T. govanianum was studied on isolated rabbit's jejunum, using acetylcholine as tissue stabiliser and verapamil as calcium channel blocker. T. govanianum attenuated the diarrhea by producing a significant decrease in the number and weight of stool, and an increase in stool latency time. T. govanianum completely inhibited both spontaneous as well as high potassium induced contractions of isolated rabbit's jejunum, which was analogous to verapamil. Moreover, T. govanianum produced a right shift in calcium concentration response curve, confirming its calcium channel blocking activity. These findings provide scientific ground to its medicinal use in diarrhea and gut spasms. Graphical Abstract: UF0001